2014
DOI: 10.1542/peds.2013-3924
|View full text |Cite
|
Sign up to set email alerts
|

Use of Neonatal Chest Ultrasound to Predict Noninvasive Ventilation Failure

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Lung ultrasound outperforms conventional radiology in the emergency diagnosis of pneumothorax and pleural effusions. In the pediatric age, lung ultrasound has been also successfully applied to the fluid-to-air transition after birth and to rapid pneumonia diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
152
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(160 citation statements)
references
References 31 publications
3
152
0
5
Order By: Relevance
“…The accuracy of LUS in estimating the need for surfactant or respiratory support has already been analyzed [7,19,20]. In those studies, LUS was confirmed to be a good tool for prediction of the need for MV, being even better than chest X-rays [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The accuracy of LUS in estimating the need for surfactant or respiratory support has already been analyzed [7,19,20]. In those studies, LUS was confirmed to be a good tool for prediction of the need for MV, being even better than chest X-rays [7].…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, LUS was confirmed to be a good tool for prediction of the need for MV, being even better than chest X-rays [7]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complications of non-invasive ventilation are mainly pressure sores of skin around the nose, ulceration and necrosis of the septum, much less likely hyperinflation of the lungs, restlessness, PTX, stomach distension or food intolerance. Non-invasive ventilation failure may be predicted by the use of neonatal chest US [52].…”
Section: Non-invasive Respiratory Supportmentioning
confidence: 99%